Adaptive power management for wireless base stations in a smart grid environment - Dusit Niyato; Xiao Lu; Ping Wang (My University, 2012)
The growing concerns of a global environmental change leads to a revolution in the way energy is utilized. In the wireless industry, green wireless communications has recently gained increasing attention and is expected to play a major role in the reduction of electrical power consumption. Actions to promote energy saving of wireless communications with regard to environmental protection are becoming imperative. To this purpose, we study a green communications system model where a wireless base station is provisioned with a combination of a renewable power source and the electrical grid to minimize the cost of power consumption as well as meet the users' demand. More specifically, we focus on adaptive power management for a wireless base station under various uncertainties, including renewable power generation, power price, and wireless traffic load. We believe that demand-side power management solutions based on the studied communication architecture is a major step toward green wireless communications.
Keywords: Provisioning; Base transceiver station; Municipal wireless network; Advanced MIMO Systems Optimization